2017
DOI: 10.1590/abd1806-4841.20175719
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant poroma and porocarcinoma

Abstract: Eccrine poromas and porocarcinomas are adnexal tumors derived from the sweat duct epithelium. However, eccrine poroma is benign in nature, whilst eccrine porocarcinoma is regarded as its malignant counterpart. We report the case of a man who presented simultaneously with an eccrine poroma and eccrine porocarcinoma. Both lesions had no clear distinctive features, enhancing the need of high-level clinical suspicion together with surgical excision and histopathology for prompt diagnosis confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The exact etiology of EPC is unclear. Some authors suggested a possible association with radiation exposure and immunosuppression, although an excessive sun exposure does not seem to be a significant risk factor [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology of EPC is unclear. Some authors suggested a possible association with radiation exposure and immunosuppression, although an excessive sun exposure does not seem to be a significant risk factor [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Debido a un amplio diagnóstico diferencial, e inclusive casos mal diagnosticados como carcinomas epiteliales de piel (4) , la biopsia es fundamental para un diagnóstico correcto de estos tumores de anexos de piel. La evaluación histopatológica muestra células tumorales atípicas con patrón de crecimiento infiltrativo, formación de estructuras lobulares, reacción desmoplásica del estroma, núcleos pleomórficos, invasión vascular y perineural (11) ; existen casos reportados de coexistencia de poroma con porocarcinoma, los cuales sugieren que derivan de estas lesiones benignas (12) . Asimismo, existen factores pronósticos de recidivas como el patrón histológico infiltrativo, profundidad del tumor > 7mm, > 14 mitosis x campo de alta potencia, invasión linfática, vascular y perineural, según los criterios de Robson (5) .…”
Section: Discussionunclassified
“…Elderly patients are the most affected, with a peak incidence between the 6 th and7th decade of life. Although it does not seem to have a predilection for sex or race, some studies indicate a slight prevalence in women [ 7 , 9 ]. The exact etiology of EPC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This elevate incidence of local recurrence may be due to a not optimal free margin at surgical excision. Lymph node metastases are present at diagnosis in 20% of cases and the incidence of visceral metastases is reported to be 10% [ 8 , 9 ]. The tumor tends to spread tangentially in the lower third of the epidermis, then after infiltrates the dermis, subcuticular fat and lymphatic system.…”
Section: Discussionmentioning
confidence: 99%